Subsequent primary neoplasms after childhood cancer therapy – design and description of the German nested case–control study STATT-SCAR - Peter Scholz-Kreisel; Cornelia Becker; Melanie Kaiser; Seyed Hamidreza Mahmoudpour; Mathias Voigt; Meike Ressing; Maria Blettner; Gabriele Calaminus; Katja Baust; Cathy Scholtes; Martin Zimmermann; Sylke Ruth Zeissig; et al. (Cancer Causes & Control, 2024)
Background Subsequent primary neoplasms (SPN) are among the most severe late effects and the second most frequent cause of death in childhood cancer patients. In this paper we introduce method and properties of the STATT-SCAR study (Second Tumor After Tumor Therapy, Second Cancer After Radiotherapy), which is a joint nested matched case–control study to evaluate the impact of chemotherapy (STATT) as well as radiotherapy (SCAR) on the risk of developing a SPN. Methods Based on the cohort of the German childhood cancer registry (GCCR), we selected patients diagnosed with a first neoplasm before age 15 or younger between 1980 and 2014. We selected those with a SPN at least half a year after the first neoplasm, and matched up to four controls to each case. Therapy data were acquired from various sources, including clinical study centers and treating hospitals. To analyze the impact of radiotherapy, organ doses were estimated by using reconstructed treatment plans. The effect of chemotherapy was analyzed using substance groups summarized after isotoxic dose conversion. Results 1244 cases with a SPN were identified and matched with 4976 controls. Treatment data were acquired for 83% of all match groups (one case and at least one control). Based on preliminary analyses, 98% of all patients received chemotherapy and 54% of all patients were treated with radiotherapy. Conclusions Based on our data, detailed analyses of dose response relationships and treatment element combinations are possible, leading to a deeper insight into SPN risks after cancer treatments. Trial registration The study is registered at the German clinical trial register (DRKS) under number DRKS00017847 [45].